Prophylactic doxazosin reduces urinary retention and promotes recovery after total joint arthroplasty: A randomized controlled trial - Ding, Zichuan; Cao, Jian; Huang, Chao; Zhou, Kai; Wang, Haoyang; Zhou, Zongke (Frontiers in Pharmacology, 2023)
Background: Postoperative urinary retention (POUR) is a common and disruptive complication following total joint arthroplasty (TJA). The aim of this study is to investigate whether doxazosin can decrease the incidence of POUR and promote recovery under the setting of modern enhanced recovery after TJA. Methods: In this randomized placebo-controlled trial, patients over 35 years of age undergoing primary unilateral TJA were recruited. Patients received doxazosin (4 mg once) or placebo 2 h before surgery. The primary outcome of interest was the development of POUR, which was diagnosed when patients with a urine volume over 400 ml or overflow incontinence. Postoperative recovery was assessed in terms of hospital length of stay after surgery, daily ambulation distance, visual analogue scale (VAS) pain score and opioid consumption. Results: A total of 170 male patients were equally randomized into Doxazosin group (mean age 54.2 ± 13.7 years, range 36–88 years) and Placebo group (mean age 54.6 ± 13.9 years, range 38–81 years). The POUR rate was significant lower in Doxazosin group (17.6%) than in Placebo group (36.5%) (p = .006). The mean LOS in the Doxazosin group was 3.1 ± 1.1 days compared to 3.6 ± 1.7 days in the Placebo group (p = .030). Doxazosin group had a longer daily mobilization distance than Placebo group on postoperative day 1 (26.8 ± 11.1 vs. 22.8 ± 9.7; p = .015). Postoperative pain assessed by VAS score and opioid usage was comparable between two groups. Conclusion: Our results support the routine use of prophylactic doxazosin in male patients to decrease POUR rate and promote postoperative recovery under the setting of modern enhanced recovery after TJA.